Complex interplay of gut microbiota between obesity and asthma in children - Hu, Mingge; Zhao, Xiaoman; Liu, Yazun; Zhou, Huan; You, Yannan; Xue, Zheng (Frontiers in Microbiology, 2023)
Obesity is an important risk factor and common comorbidity of childhood asthma. Simultaneously, obesity-related asthma, a distinct asthma phenotype, has attracted significant attention owing to its association with more severe clinical manifestations, poorer disease control, and reduced quality of life. The establishment of the gut microbiota during early life is essential for maintaining metabolic balance and fostering the development of the immune system in children. Microbial dysbiosis influences host lipid metabolism, triggers chronic low-grade inflammation, and affects immune responses. It is intimately linked to the susceptibility to childhood obesity and asthma and plays a potentially crucial transitional role in the progression of obesity-related asthma. This review article summarizes the latest research on the interplay between asthma and obesity, with a particular focus on the mediating role of gut microbiota in the pathogenesis of obesity-related asthma. This study aimed to provide valuable insight to enhance our understanding of this condition and offer preliminary evidence to support the development of therapeutic interventions.